PREVALENSI MIGREN DAN KOMORBIDITAS DEPRESI PADA MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Tirtha, Putu Bagus Bramanthana; Adnyana, I Made Oka; Putra, Ida Bagus Kusuma; Laksmidewi, Anak Agung Ayu Putri (E-Jurnal Medika Udayana; Vol 11 No 2 (2022): E-Jurnal Medika Udayana, 2022)
Introduction : Depression is one of the world’s major causes of disability, and the comorbidity of depression with migraine can worsen the patient's prognosis. By studying this comorbidity, the treatment quality can be improved. In addition, data regarding comorbidity of migraine and depression among students in Bali are still limited. Method : This is a descriptive analytic cross-sectional research. The sample population are pre-clinical students of the Undergraduate Program of Medicine and Medical Profession, Faculty of Medicine, Udayana University, aged 18 to 22 years. The total sample is 100 people. The purpose of this research is to describe the prevalence of migraine and depression in the sample population, and to understand whether there is a relationship between the prevalence of migraine and the prevalence of depression. This study used a questionnaire containing questions about headache status, depression status, and confounding variables status (gender, menstrual period, eating and drinking patterns, and socioeconomic status). Result and discussion : Migraine prevalence is 7%, and depression prevalence is 4%. 42,9% of the people who have migraine also have depression. 1,1% of the people who did not have migraine have depression. 2-sided P = 0.001 is derived from Fischer’s Exact Test. Conclusion : There is a relationship between migraine prevalence and depression prevalence.